Survival Analysis of Culinary Business in Palembang and Bandarlampung - Lukman, Iing; Oktarina, Devi; Shinta, Dayu Renanda; Sariningsih, Eka; Ariningrum, Hardini (Technium Business and Management, 2023)
Agriculturally based culinary businesses have been spread across the country nowadays, included in Indonesia. The objective of this paper is to deal with the survival analysis of those kinds’ businesses, in Palembang and Bandar Lampung or to find out what factors can make a business venture survive, and what are the prominent competitive risk factors that affect the business venture. The methodology of collecting samples were conducted by purposive sampling, which is at least 50 culinary sellers taken each as samples from both cities. The samples involving Demography data and variables around culinary selling activities. The observation was conducted at least twice, at the beginning of the survey and the end of the survey. The Survival Analysis of Cox regression for competing risk was assigned to data analysis. Therefore, the results from both cities were compared. The determination of the first type of failure and second type of failure namely the lacked capital and the rise of the materials price are or high inflation correctly fitted to the real situation for culinary sellers either in Bandar Lampung or Palembang. The covariates which is significant to the contribution of the survival times of their period of business is sharing the small money to the poor.